The tadpole of Amazophrynella manaos Rojas, Carvalho, Gordo, Ávila, Farias and Hrbek, 2014 (Anura, Bufonidae) from the type locality and adjacent regions at Central Amazonia, Brazil - Menin, Marcelo; Pegorini, Reysi Jhayne; de Carvalho, Vinicius Tadeu; Rojas, Rommel Roberto; Gordo, Marcelo (Zootaxa, 2014)
The genus Amazophrynella, as currently recognized (Fouquet et al. 2012a, b), is represented by four nominal species (Frost 2014; Rojas et al. 2014) but the tadpoles of only one species, Amazophrynella minuta (Melin) from Ecuador, have been described (Duellman & Lynch 1969; Duellman 1978). Amazophrynella manaos Rojas, Carvalho, Gordo, Ávila, Farias and Hrbek, 2014 occurs in the leaf litter of terra firme forest in the southwestern part of the Brazilian Guiana region (Rojas et al. 2014). The tadpole of this species was briefly described in diagrammatic drawings by Hero (1990) as Dendrophryniscus minutus. Herein, we provide a detailed description of this tadpole based on individuals at 12 stages of development collected in five different sites, including the type locality, at Central Amazonia, Brazil.